2019
DOI: 10.1093/dote/doz092.159
|View full text |Cite
|
Sign up to set email alerts
|

P159 the Impact of Postoperative Complications on Long-Term Survival and Disease Recurrence Following Oesophago-Gastric Cancer Resection

Abstract: Aim Postoperative complications following the resection of oesophago-gastric carcinoma can result in considerable early morbidity and mortality, however the long-term effects are less clear. Literature reports are mixed, so it remains unclear if complications reduce survival, as has been demonstrated in colorectal cancer. Background & Methods Some 1100 patients who underwent oesophago-gastric resection between 2006-16 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Morbidity after surgery was associated with worse long-term outcomes such as OS and RFS in patients with various cancers, such as esophageal cancers, colorectal cancers, and metastatic liver cancers 23–26 . Recently, similar results have been reported in patients with HCC who underwent hepatectomy.…”
Section: Discussionmentioning
confidence: 71%
“…Morbidity after surgery was associated with worse long-term outcomes such as OS and RFS in patients with various cancers, such as esophageal cancers, colorectal cancers, and metastatic liver cancers 23–26 . Recently, similar results have been reported in patients with HCC who underwent hepatectomy.…”
Section: Discussionmentioning
confidence: 71%
“…Leakage associated with grade III-V complications, according to the Clavien-Dindo grading system 16,17 , was defined as severe AL, and that associated with less severe complications (grade I-II) as non-severe AL. All patients who died within 30 days of surgery were excluded from the adjusted analyses of long-term survival, consistent with previous studies 9,18 .…”
Section: Definition Of Anastomotic Leakmentioning
confidence: 78%
“…Multiple studies have also suggested that splenectomy is closely associated with increased postoperative complication rates and mortality, and postoperative complications, especially intra-abdominal infectious complications, can further affect the OS and DFS of patients with GC. [14][15][16] Therefore, based on the proficient mastering of LSPSHL, we conducted the Fuges-02 RCT to explore the specific efficacy of splenic hilum lymphadenectomy for patients when avoiding splenectomy. In addition, 85.2% of the patients enrolled in this study had stage II or III tumors, and the incidence rate of SHLN metastasis (13.3%) was higher than the rate of 2.4% reported in the JCOG0110 study.…”
Section: Discussionmentioning
confidence: 99%